A Dieting Facilitator on the Fridge Door: Can Dieters Deliberately Apply Environmental Dieting Cues to Lose Weight? - Stämpfli, Aline E.; Stöckli, Sabrina; Brunner, Thomas A.; Messner, Claude (Frontiers in Psychology, 2020)
Individuals exposed to dieting-related environmental cues have been repeatedly shown to be better able to resist tempting food. This especially applies to restrained eaters who hold a chronic dieting goal. Thus far, mainly short-term effects of environmental dieting cues have been examined and the individuals were typically unaware of being influenced. Yet, it is unclear whether individuals can deliberately apply environmental dieting cues for themselves to facilitate the pursuit of the longer-term goal of losing weight. The present longitudinal study applied a 2 (cue: visually dieting-related vs. visually neutral cue) × 2 (awareness: being aware vs. not being aware of the cue’s facilitating influence) between-subjects design for six months (N = 166 participants who started the study; Mage = 47.85 years; 69.9% female; MBMI = 29.07 kg/m2). Our results provide preliminary indications that cue, awareness, and restrained eating interact. The results suggest that high (vs. low) restrained eaters could deliberately apply environmental dieting cues for themselves to facilitate losing weight. However, further studies are needed to explore the effects of environmental dieting cues over a longer period of time.